Embedded silicene nanostructures in partly-dehydrogenated polysilane. Issue 16 (5th April 2017) - Li, Xiuling; Zeng, Xiao Cheng; Wu, Xiaojun
Abstract : First-principles calculations reveal that embedded silicene nanoribbons with novel electronic properties can be obtained by partly dehydrogenating polysilane sheets. Abstract : Developing freestanding silicene nanostructures with tunable electronic and magnetic properties is of particular importance for their applications in nanoelectronics, but still faces big challenges. On the basis of first-principles calculations, here we predict that embedded silicene nanoflakes and nanoribbons can be realized by partly dehydrogenating a freestanding polysilane (Si6 H6 ) sheet. Born–Oppenheimer molecular dynamics simulations indicate that the embedded silicene nanostructures show good thermal stability at 500 K. In particular, the embedded silicene nanostructures exhibit similar electronics properties to those of isolated ones. These findings imply a practical solution to produce embedded silicene nanostructures from partly dehydrogenated freestanding polysilane.